Fektivitas Model Pembelajaran Missouri Mathematics Project (MMP) terhadap Kemampuan Penalaran Matematis Siswa di Kelas VIII SMP Swasta PAB 13 - Elmaida Surya; Ainul Marhamah Hasibuan; Azizah Yusra Amaliyah Harahap (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
The study evaluates the effectiveness of the Missouri Mathematics Project (MMP) learning model in enhancing the mathematical reasoning abilities of eighth-grade students at PAB 13 Private Middle School. A quantitative approach with a One Group Pretest-Posttest experimental design is employed. The sample consists of 30 students selected randomly. The instrument used is a descriptive test aligned with mathematical reasoning indicators, such as constructing arguments, drawing conclusions, verifying truth, and performing mathematical manipulation. This test is administered before and after the intervention. Data analysis involves a normality test and a paired sample t-test using the latest version of SPSS software. The results show that the data follow a normal distribution and there is a significant difference between the pretest and posttest scores (Sig. < 0.05). The average score increased from 26.50 to 77.50 with a difference of 51.00 points. These findings demonstrate that the implementation of the MMP model is effective in improving students' mathematical reasoning skills and encouraging their activeness and engagement in learning. The MMP model is recommended for application to mathematics materials that require conceptual understanding and in-depth logical thinking skills.